Recreational Screen Time Activities and Depressive Symptomatology Among Adolescents: A Longitudinal Investigation of Cognitive, Behavioural, Affective, and Interpersonal Factors as Mediators and Moderators - Murray, Marisa (Université d'Ottawa / University of Ottawa, 2018)
Recreational screen time activities (e.g., computer use, television viewing, and videogame engagement) have become increasingly embedded in modern day culture, posing both physical and psychological health consequences (Babic et al., 2017; Goldfield et al., 2013). Despite the established link between recreational screen time and adolescent depressive symptomatology, little is known about mechanisms that may explain or influence this relationship. The overarching objective of the present dissertation, which includes two separate studies, was to examine cognitive, behavioural, affective, and interpersonal factors associated with the relationship between adolescents’ total daily recreational screen time activities and depressive symptomatology over time. The dissertation includes archival data from the Research on Eating and Adolescent Lifestyle (REAL) Study, which examined a large sample of students from the National Capital Region of Canada. Both Study 1 and Study 2 examined a subsample of these students. Given that exposure to screen time occupies up to 10 hours of Canadian children and adolescents’ waking hours (Active Healthy Kids Canada, 2013; Leatherdale & Ahmed, 2011; Leatherdale & Harvey, 2015), the independent variable examined in the model was total daily recreational screen time activities. Because trajectories of depressive symptomatology typically increase during adolescence (Duchesne & Ratelle, 2014), the dependent variable examined in the model was depressive symptomatology. The time points spanned over 7 years. The purpose of Study 1 was to test a prospective longitudinal path analysis model. The model examined the relationship between total daily recreational screen time at baseline (T0) and depressive symptomatology at Time 4 (T4), with body image and disordered eating behaviours at Time 2 (T2) as potential mediating variables. The final sample included 304 English-speaking students (194 females, Mage = 13.40 years, SD = 1.10). Total daily recreational screen time at T0 was significantly predictive of depressive symptomatology at T4. Appearance (dis)satisfaction at T2 mediated the relationship between total daily recreational screen time at T0 and depressive symptomatology at T4. Total daily recreational screen time at T0 was significantly predictive of emotional eating and decreased body image satisfaction at T2. Restrained eating and appearance satisfaction were negatively associated with depressive symptomatology at T4. Results were independent of age and depressive symptomatology at T0. The purpose of Study 2 was to test a longitudinal moderation model including total daily recreational screen time at T0 and depressive symptomatology at T4, with attachment style, coping style, and perceived social support at T0 as potential moderating variables. The final sample included 170 English-speaking students (106 females; Mage = 13.01, SD = 0.96). Contrary to expectation, attachment style, coping style, and perceived social support did not moderate the relationship between total daily recreational screen time at T0 and depressive symptomatology at T4. However, insecure attachment was identified as a risk factor for depressive symptomatology among males. A trend emerged in that avoidance-oriented coping appeared to be a risk factor for depressive symptomatology among females and a protective factor for males. There was also a three-way interaction between total daily recreational screen time, gender, and perceived social support. That is, when perceived social support was high, higher levels of total daily recreational screen time at T0 was associated with higher levels of depressive symptomatology at T4 for both males and females, but the relationship was significant for males only. Findings from the present dissertation offer important theoretical, methodological, and clinical implications.
Keywords: Screen time; Adolescents; Depression